Gene therapy for lower urinary tract dysfunction. (7th November 2012) - Yoshimura, Naoki; Miyazato, Minoru; Sasaki, Katsumi; Yokoyama, Hitoshi; Oguchi, Tomohiko; Chancellor, Michael B; Funahashi, Yasuhito
Abstract Lower urinary tract dysfunction is caused by functional and pathophysiological alterations of the peripheral organs, including the urothelium and detrusor smooth muscle, as well as peripheral and central nervous systems. Recent research in this field has increased our understanding of the mechanisms of lower urinary tract dysfunction, and new drugs have been developed, leading to increased treatment options and changing medical care for lower urinary tract symptoms. Nevertheless, clinicians still often experience refractory and treatment‐resistant cases against conventional therapeutic modalities. For such cases, gene therapy targeting for the lower urinary tract and its afferent pathway is anticipated to offer a new therapeutic approach. Therefore, in this article, we review the possibility and current status of gene therapy for lower urinary tract dysfunction.